Determinants of Strategy Implementation in Agricultural Development Corporation - Bundotich, Samuel Kipngetich Kiptarus; Nzulwa, Dr. Joyce; Mburu, Dr. David Kiarie (IJRDO - Journal of Applied Management Science, 2016)
Current research indicates that the success rate in implementing strategies by organizations stands between 10% and 30%. While strategy formulation is paramount and widely researched, little research has been done on strategy implementation hence the need to carry out more research work in this area in order to build more knowledge. This study, therefore, concentrated on determinants of strategy implementation in the Agricultural Development Corporation (ADC). A descriptive research design was used in the study, with a population of 340 employees of ADC. These comprised of 14 senior managers, 90 middle level managers and 236 low level employees. Stratified sampling was conducted and a 20% sample resulting to 68 respondents was drawn. The study used a questionnaire with closed and open-ended questions to collect primary data. Secondary data were collected from the ADC strategic plan: 2015-2019, consolidated annual reports & financial statements: 2012-15, strategic plan review report of 2013 and progress reports which describe strategy implementation process in the corporation. The researcher checked the completed questionnaires for completeness and consistency of information. The quantitative data were coded and analyzed using SPSS (statistics Package for Social Sciences) and presented using tables, charts, and graphs with respective interpretation. Qualitative data were grouped into common themes based on the research variables. The research found that strategic communication supported strategy implementation at the Agricultural Development Corporation. The evaluation of effect of strategic capability in the corporation established that the variable supported strategy implementation in the corporation. Similarly the study found that strategic flexibility supported strategy implementation at Agricultural Development Corporation. The study found a strong positive relationship between strategy implementation and communication process and organizational capability. A weak positive relationship was established between strategy implementation and strategic flexibility. The study therefore, recommended that other state corporations implementing their strategic plans need to give attention to strategic communication, organizational capability and strategic flexibility.